(-3xy)(7xy)=

Simple and best practice solution for (-3xy)(7xy)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-3xy)(7xy)= equation:


Simplifying
(-3xy)(7xy) = 0

Remove parenthesis around (-3xy)
-3xy(7xy) = 0

Remove parenthesis around (7xy)
-3xy * 7xy = 0

Reorder the terms for easier multiplication:
-3 * 7xy * xy = 0

Multiply -3 * 7
-21xy * xy = 0

Multiply xy * xy
-21x2y2 = 0

Solving
-21x2y2 = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-21'.
x2y2 = 0

Simplifying
x2y2 = 0

The solution to this equation could not be determined.

See similar equations:

| 14n+q=rt-4n | | -10+9x=125 | | 3x+48=2x+24 | | 40x+9.6x=644.80 | | 0=-(x-3)(x-3)+1 | | 5.50(h)=71.50 | | 5w-4w+2w=9 | | 3x+9-9(x+1)=2x+5 | | -5/12*27/15= | | 12+5x=68 | | 15y+17=13y+14 | | 2x-6=5x+22 | | 40-14x=21x-100 | | 0.10+0.05(52-x)=4.50 | | 7=6m-2m+3 | | 7x(6+8)=7*6+7x | | 16x-6153=1143 | | 4(4x-7)(2x+7)=0 | | 170+106+17x=1600 | | x+-4+2x=1 | | s-10=20.68 | | 4x-84=9x+3 | | 8-4u=8u-5 | | 86x+9648=48090 | | -39=-18w-21 | | 50-(x*3)=(7*x)+80 | | 3.5r=196 | | -16x+12=-12x-16 | | 8(x^2)+6=0 | | (x+5)(5x-7)=0 | | 1+0.80=2+0.75 | | 4-0.9(z-14)=0.5(4z-14) |

Equations solver categories